Creating a Framework for Sustainable Research and Extension Engagements in an Education Institution Funded by the Local Community - Bastida, Ernesto L., Jr.; Alvaran, Cecilia Raquel C.; De Lara, Rudy Bhonne R.; Abargos, Jerbert M.; Saysi, Jhonies G.; Auxillos-Cualbar, Kenneth A.; Millo, Lodelio D. (ASEAN Journal of Community Engagement, 2024)
The role of higher educational institutions (HEI) in securing a sustainable future for all is not only limited to quality instruction but also includes development-focused research and need-based extension services. Pursuant to national and international commitment and policies, these three fundamental functions of HEIs are mandated to be aligned with the 17 Sustainable Development Goals to intensify their roles in knowledge creation and commercialization while protecting the planet. The City of Dasmariñas, through the Kolehiyo ng Lungsod ng Dasmariñas (KLD) as its locally funded HEI, has taken initial steps to strengthen its sustainable governance through competitive research initiatives and extension programs. Using an exploratory research design, the sustainability efforts initiated by this locally funded HEI were revisited and analyzed. The responses of faculty members, parents, students, policymakers, local government officials, scientific communities, and other stakeholders from various qualitative data collection methods were carefully examined. A series of sustainability planning workshops was then conducted. The results revealed that all research and extension activities of KLD hinged on the localized SDGs. The participants highlighted the importance of internal and external funding in sustaining a strong commitment to research and extension. The competitive incentive system and numerous partnerships with other organizations and institutions were also considered enablers for the institution to create projects that would bring positive effects to the local community. The results were used to develop a sustainability-informed research and extension framework containing a research agenda, institutional actors, sustainability metrics, scope of effects, priority areas, core characteristics and principles, and enabling mechanisms.